A Systematic Review of Sensitivity Analysis in Building Energy Modeling: Key Factors Influencing Building Thermal Energy Performance - Rajendra Roka; António Figueiredo; Ana Vieira; Claudino Cardoso (Energies)
Improving building thermal energy performance is essential to reducing energy consumption, minimizing carbon emissions, and enhancing occupants’ thermal comfort. For this purpose, there is an increasing research interest in this field of building energy performance. This review aims to present a precise and systematic overview of the sensitivity analysis in optimizing the thermal energy performance of buildings. The investigation covers various aspects, including sensitivity analysis techniques, key measures and variables, objectives and criteria, software tools, optimization methods, climate zones, building typology, and climate change effects. The findings reveal that sensitivity analysis is a powerful technique for optimizing energy performance and identifying adaptive strategies such as dynamic shading, reflective coatings, and efficient HVAC set points to address climate change. Most of the study also highlights that the temperature set point is the key influential parameter in both heating-dominant and cooling-dominant climate zones. This review offers critical insights on advancing sustainable building design, informing policy, and guiding future research in energy-efficient building solutions.